Health Insurance Benefit Mandates and Firm Size Distribution. Issue 2 (15th August 2016) - Bailey, James; Webber, Douglas
Abstract: By 2010, the average U.S. state had passed 37 health insurance benefit mandates (laws requiring health insurance plans to cover certain additional services). Previous work has shown that these mandates likely increase health insurance premiums, which in turn could make it more costly for firms to compensate employees. Using 1996–2010 data from the Quarterly Census of Employment and Wages and a novel instrumental variables strategy, we show that there is limited evidence that mandates reduce employment. However, we find that mandates lead to a distortion in firm size, benefiting larger firms that are able to self‐insure and thus exempt themselves from these state‐level health insurance regulations. This distortion in firm size away from small businesses may lead to substantial decreases in productivity and economic growth.